2020
DOI: 10.1002/jcsm.12614
|View full text |Cite
|
Sign up to set email alerts
|

Associations of low handgrip strength with cancer mortality: a multicentre observational study

Abstract: Background Handgrip strength (HGS) is associated with poor clinical outcomes, including all-cause, non-cardiovascular, and cardiovascular mortalities. The published cutoff points for HGS are mostly based on community populations from Western countries, lacking information on cancer patients from China. The objective of this study was to establish sex-specific cutoff points for Chinese cancer patients and investigate the effect of low HGS on cancer mortality. Methods We did a retrospective cohort study of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 48 publications
6
52
3
4
Order By: Relevance
“…In contrast, participants in our study were general inpatients and suffered from various types of disease, not exclusively from cancer. In our study, the prevalence of low handgrip strength was 49.57%, higher than in the study by Zhuang et al ( 13 ) (25.7%). The difference may be due to the fact that the average age in our study was much higher, at 72.39 vs. 58 years old.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In contrast, participants in our study were general inpatients and suffered from various types of disease, not exclusively from cancer. In our study, the prevalence of low handgrip strength was 49.57%, higher than in the study by Zhuang et al ( 13 ) (25.7%). The difference may be due to the fact that the average age in our study was much higher, at 72.39 vs. 58 years old.…”
Section: Discussioncontrasting
confidence: 79%
“…In comparison, this meta-analysis only included one study on older Chinese adults, with only 99 participants. A recent larger study on the Chinese population conducted by Zhuang et al ( 13 ), exploring the correlation between handgrip strength (HGS) and mortality, showed that older adults with low HGS had a strongly increased risk of overall cancer mortality. In contrast, participants in our study were general inpatients and suffered from various types of disease, not exclusively from cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partindo desse pressuposto, Zhuang et al, 17 demostraram que pacientes com diferentes tipos de câncer, incluindo o câncer mama eram mais propensos a terem baixa FPM. Corroborando com esses achados, Christensen et al, demostraram que pacientes com câncer tem prejuízos significativos na força muscular, independentemente do estágio da doença, quando comparado a indivíduos saudáveis de mesma faixa etária, gênero, índice de massa corporal e nível de atividade física.…”
Section: Discussionunclassified
“…Pre-transplant physical function has been reported to be related to post-transplant survival [2,3], and muscle strength is a factor that directly affects these physical functions. Although muscle strength has been reported to be associated with survival in healthy adults [4] and in patients with cancer [5], there are no reports on its association with long-term prognosis in allo-HSCT. As a factor related to muscle strength, skeletal muscle mass measured by computed tomography (CT) imaging has been reported to be associated with long-term prognosis after transplantation [6][7][8].…”
Section: Introductionmentioning
confidence: 99%